AMPLIFICATION IN SERVICE SUPPLY CHAINS: AN EXPLORATORY CASE STUDY FROM THE TELECOM INDUSTRY - AKKERMANS, HENK; VOS, BART (Production and Operations Management, 2003)
Evidence on the impact of amplification effects on supply chain performance primarily has been derived from studies in manufacturing industries. In this article we reported on a case study from the telecommunication industry and aimed to analyze relevant root causes and associated countermeasures of the amplification phenomenon in service supply chains. Our case findings confirm the occurrence of upstream amplification of workload in the service supply chain, workload being a more appropriate measure for amplification effects in service supply chains than inventory levels. Not all of the root causes for amplification effects known from research in manufacturing environments were found to apply in this particular service context, especially those related to the use of inventory. In addition, our telecom case study highlighted a new root cause for amplification: interactions of high workloads and reduced process quality that start reinforcing each other once workloads pass a certain threshold. In this particular case, many of the known countermeasures to eliminate amplification did not apply, because of the specific characteristics of the service process, or yielded only limited results. A potentially very powerful countermeasure identified was to implement quality improvements throughout the service chain. This quality dimension links our research to the literature on service management in general, where service quality is on top of the research agenda.